PENGARUH PENGETAHUAN AKUNTANSI, PENGALAMAN USAHA DAN SKALA USAHA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA UMKM DI KECAMATAN TAWANGMANGU KARANGANYAR - Linda Oktaviana; Indra Lila Kusuma; Rukmini Rukmini (Jurnal Akuntansi dan Pajak, 2023)
This study aims to determine the factors that influence the use of accounting information on SMEs in the Tawangmangu District, Karanganyar Regency. The independent variabels in this study are accounting knowledge, business experience and business scale. While the dependent variable is the use of accounting information for SMEs in Tawangmangu District, Karanganyar Regency. The sample used in this study were 85 SMEs in the trade sector in Tawangmangu District, Karanganyar Regency. Data was collected by d istributing questionnaires to respondents. The analysis used is multiple regression analysis with SPSS version 28. The results of this study indicate that there are only two of the three variables that have a significant effect on the use of MSME accounting information in Tawangmangu District, Karanganyar Regency, namely accounting knowledge and business scale.